Dental and oral health e-book on knowledge of debris index for elementary school students - Adela, Azahra Nur; Kristianto, Jusuf; Lestari, Syifa Yulia (Center of Excellent (Pusat Unggulan Iptek), 2024)
Background: Based on information from Basic Health Research in 2013, around 28.9% of children aged 5-9 years and 25.2% of children aged 10-14 years experienced dental and oral health problems. Especially in childhood, dental caries is a problem that must be avoided, especially when they attend elementary school. Therefore, it is important for us to provide knowledge about how important it is to maintain healthy teeth in children. It is hoped that the educational program can increase public awareness about the importance of maintaining dental and oral health and motivate them to actively maintain their own dental and oral health. Providing e-books about dental and oral health as a learning tool is one innovative way to change children's behavior in maintaining dental and oral health. Objective: To analyze the effectiveness of dental health e-books on knowledge and debris index in elementary school students. Method: This research uses a quasi experimental research design. This research was conducted on class V students of SDN Krukut 03 Limo Depok. The number of samples used was 54 people using purposive sampling technique. Data collection was carried out by direct examination and filling out a questionnaire sheet. Data were analyzed using the paired sample t-test. Results: Of the 54 samples, the average debris index score before counseling was 1.59, medium criteria and after counseling the average debris index was 0.95, medium criteria with the results of paired sample t-test p <0.001. There is a difference in the average knowledge score, namely from the previous 75.85, sufficient criteria to 88.52, good criteria, with the results of paired sample t-test p <0.001. Conclusion: Dental and oral health e-books are effective in increasing knowledge and reducing debris index scores in elementary school students.